南极中山站生活污水及石油污染区域细菌多样性分析 - 林曦 (2007)
随着南极研究的深入进行，人类的科学考察活动对南极环境造成的影响越来越引起重视。本文针对南极中山站周围生活污水、石油污染两大问题进行分析，采集了2005、2006两个年份的相关区域的环境样品，研究了样品中微生物多样性、群落结构，及其逐年的变化；建立了石油污染降解相关的xylE基因的定量PCR检测技术。为我国在南极活动中的环境评估，科考活动方案制订，以及参与国际南极活动提供科学依据。 以南极中山站排污口及其右侧50米处土壤为研究对象，经土样采集、DNA提取、纯化后，使用341f+534r通用引物进行扩增，得到包含V3可变区的16SrDNA片段。经变性梯度凝胶电泳（DGGE）及测序分析发现，相较于. More and more attention has been attracted to the Antarctic environmental contamination caused by human activities, as the study about Antarctica developed. Aiming for a better understanding about the sewage and oil contamination, we collected soil samples from suspected sites in both 2005 and 2006, and studied the microbial diversity, community structure and their changes between two years. Moreo. 学位：理学硕士 院系专业：生命科学学院生物学系_生物化学与分子生物学 学号：200426103